Camino Island - Grisham, John (Grisham, John. Camino series., 2017)
Bruce Cable owns a popular bookstore in the sleepy resort town of Santa Rosa on Camino Island in Florida. He makes his real money, though, as a prominent dealer in rare books. Very few people know that he occasionally dabbles in the black market of stolen books and manuscripts. Mercer Mann is a young novelist with a severe case of writer's block who has recently been laid off from her teaching position. She is approached by an elegant, mysterious woman working for an even more mysterious company. A generous offer of money convinces Mercer to go undercover and infiltrate Bruce Cable's circle of literary friends, ideally getting close enough to him to learn his secrets. But eventually Mercer learns far too much.